2016
DOI: 10.1097/ico.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cystoid Macular Edema After Descemet Membrane Endothelial Keratoplasty as a Staged and Solitary Procedure

Abstract: The incidence of postoperative CME after DMEK is similar in the setting of recent or remote cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 24 publications
4
16
1
Order By: Relevance
“…In a large prospective study involving 155 eyes, Heinzelmann et al 11 reported a post-DMEK CME incidence of 13%, with no significant difference in the CME incidence after DMEK and triple-DMEK. More recently, Hoerster et al 12 reported a CME incidence of 12% in a study that included 75 eyes, and Flanary et al 13 reported an incidence of 7.5% in a study that included 173 eyes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large prospective study involving 155 eyes, Heinzelmann et al 11 reported a post-DMEK CME incidence of 13%, with no significant difference in the CME incidence after DMEK and triple-DMEK. More recently, Hoerster et al 12 reported a CME incidence of 12% in a study that included 75 eyes, and Flanary et al 13 reported an incidence of 7.5% in a study that included 173 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the incidence of CME after DMEK is generally high and that there is not a “typical” patient who develops it. Flanary et al 13 examined post-DMEK CME incidence in patients who had recently (between 2 wk and 6 mo) and remotely (>6 mo) undergone cataract surgery. In agreement with our findings, these pseudophakic eyes had a CME incidence of 7.5%, with no significant difference between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the typical approach to cases of concurrent cataract and corneal edema at our institution. 1 Advantages of staging the DMEK surgery include improved intraoperative iris control, which we felt was a distinct advantage given the limited predictability of iris behavior after iridectomy in the context of the patient's iridoschisis.…”
Section: Discussionmentioning
confidence: 99%
“…One month later, uncomplicated DMEK was performed in the right eye using our previously published technique. 1 Graft edge lifts were not noted. One month after DMEK in the right eye, BCVA was 20/30, slit lamp examination showed an attached DMEK graft with clear overlying stroma, and CCT was 538 μm ( Fig.…”
Section: Case Reportmentioning
confidence: 99%